A study on service quality in public and private case study: Sarawak General Hospital and Normah Specialist Centre / Fatimah Munil & Firna Erkafitrie Yusuf - Munil, Fatimah; Yusuf, Firna Erkafitrie (2012)
This study compared the service quality provided by public and private hospitals, between Sarawak General Hospital and Normah Specialist Centre. The patient’s perceptions were sought on five dimension of service quality including tangibility, reliability, responsiveness, empathy and assurance. The objective of this study is to determine the gap in service quality and to determine which service quality dimension is emphasized by the hospitals. This study is covered the outpatients of both hospitals. In the conclusion, factors analyzed revealed that there is significant difference in the service quality between the hospitals and the responsiveness dimension is the least dimension emphasized by the hospitals. Findings are important for the future researcher and policy makers.